Framing Analysis of Belt and Road Initiative - Anunne, Uchenna Kingsley; Thuy, Pham Ngoc Phuong; Yan, Julia Tan Yin; Lifeng, Yan (European Scientific Journal, ESJ, 2019)
In 2013, Chinese president, Xi Jinping, announced the Belt and Road Initiative (BRI) to his audience in Kazakhstan. He stated that this will involve the construction of roads, railways, and even special trade corridors, among others along the ancient Silk Road in a bid to foster economic, political, and social relationship between China and partner countries. This paper focuses on analyzing how leading newspapers in Nigeria, Malaysia, and Vietnam, namely The Sun, Vanguard, The Punch, The Nation, NewStraits Times, Malay Mail, Business Insider, The Star, Saigon Times and Vietnamnet Bridge, have framed and communicated this multi-national project to their various audiences six years after Xi’s announcement. Working on 200 editorial contents published between May 2017 and March 2019 across the selected newspapers, this explores how they framed BRI. We found that while most of the reports have framed BRI positively, others are framed to reflect cautious optimism. We suggest that BRI managers should take necessary steps to engage the media, policy makers, and other stakeholders to properly educate them on the vision and mission of the initiative.